Eugenosedin-A ameliorates hyperlipidemia-induced vascular endothelial dysfunction via inhibition of α1-adrenoceptor/5-HT activity and NADPH oxidase expression - Kuo-Ping Shen; Hui-Li Lin; Wen-Tsan Chang; Jou-Chun Lin; Li-Mei An; Ing-Jun Chen; Bin-Nan Wu (Kaohsiung Journal of Medical Sciences, 2014)
Eugenosedin-A (Eu-A) effects on vascular endothelial dysfunction and oxidative stress in a hyperlipidemic rat model were investigated. Rats were randomly divided into four groups: two control groups and two treatment groups. The control rats received a regular diet or high fat diet (HFD); the treatment rats fed received an HFD with 5 mg/kg Eu-A or atorvastatin for 10 weeks. No changes in serotonin levels were observed in the four groups; norepinephrine levels were enhanced in the HFD group which was attenuated by Eu-A and atorvastatin. In the HFD group, the vascular reactivity was increased by vasoconstrictors (5-nonyloxytryptamine, 5-HT, and phenylephrine) and decreased by an endothelium-dependent vasorelaxant, carbachol. Protein levels of α1-adrenergic receptors (not 5-HT1B/2A), reactive oxygen species (ROS) p47phox, p67phox, and gp91phox, and oxidative damage markers 3-nitrotyrosine (3-NT) and 4-hydroxy-2-nonenal (4-HNE) were increased, but endothelial nitric oxide synthase (eNOS), P-eNOS and vasodilator-stimulated phosphoprotein phosphorylation (P-VASP) were decreased. Catalase and superoxide dismutase (SOD-1 and SOD-2) proteins were increased, but glutathione peroxidase (GPx) was decreased in the aorta. Eu-A and atorvastatin reduced vasoconstrictor-induced aortic contractions that might be related to 5-HT1B/2A and α1-adrenergic receptors inhibitory activities. Eu-A and atorvastatin improved eNOS/P-eNOS, P-VASP, GPx, and malondialdehyde (MDA) levels, and decreased ROS and oxidative damage markers. Taken together, we suggest that Eu-A can ameliorate hyperlipidemia-induced vascular endothelial dysfunction and oxidative dysregulation.